Women and the management of acute coronary syndrome - Ostadal, Petr; Ostadal, Bohuslav (Canadian journal of physiology and pharmacology, 2012)
Coronary heart disease (CHD) is the leading cause of morbidity and mortality in both men and women in the developed countries. Despite this fact, females are still under-represented in the majority of clinical trials. At the present time, only limited evidence is available with respect to the female-specific aspects of pathogenesis, management, and outcomes in acute coronary syndrome (ACS). Women less frequently undergo coronary intervention, and a lower proportion of women receive evidence-based pharmacotherapy, compared with men. It has been shown that women benefit from an invasive approach and coronary intervention in ACS as much as men, despite their advanced age and higher rate of bleeding complications. Also, administration of beta-blockers, ACE-inhibitors, and intensive statin therapy is associated with a comparable reduction of cardiovascular event rates in women and men. On the other hand, women may profit less than men from fibrinolytic or glycoprotein IIb/IIIa inhibitor therapy. Both sexes benefit equally from aspirin therapy, whereas contradictory data are available on the efficacy of clopidogrel in women. There is an urgent need for intensive research in the development of female-specific therapeutic strategy in ACS, even though the detailed mechanisms of sex differences are still unknown.
Keywords: antikoagulancia; klinické zkoušky jako téma; Acute Coronary Syndrome; Clinical Trials as Topic; Female; beta blokátory; výsledek terapie; ženské pohlaví; Anticoagulants; lidé; renin-angiotensin systém; koronární angioplastika; Renin-Angiotensin System; Platelet Glycoprotein GPIIb-IIIa Complex; Treatment Outcome; statiny; Sex Characteristics; Percutaneous Coronary Intervention; Male; Hydroxymethylglutaryl-CoA Reductase Inhibitors; medicína založená na důkazech; pohlavní dimorfismus; trombocytový glykoproteinový komplex IIb-IIIa; Adrenergic beta-Antagonists; akutní koronární syndrom; mužské pohlaví; Evidence-Based Medicine; Humans